The accidental reef and other ecological odysseys in the Great Lakes - Heasley, Lynne (Book collections on Project MUSE., 2021)
"This book takes readers on journeys through the Great Lakes, alongside fish and fishers, scuba divers and scientists, toxic pollutants and threatened communities, oil pipelines and invasive species, Indigenous peoples and federal agencies, in order to grapple with the legacies and alternative futures that come from their abundance of natural wealth"--